Pemenuhan Hak Kesehatan bagi Wargabinaan di Lembaga Pemasyarakatan Dihubungkan dengan Undang-Undang Nomor 12 Tahun 1995 tentang Pemasyarakatan - Muhammad Firman Ardiansyah; Chepi Ali Firman Zakaria (Bandung Conference Series: Law Studies, 2022)
Abstract. In the process of enforcing the law for criminals to be integrated back in the community through the Penitentiary is a place to carry out the construction of Prisoners and Correctional Students. The manifestation of Article 12 of Law No.12 of 1995 on Correctional Services requires that every inmate get a decent place to live, the right to nutritious food and the right to health services. Terkait with health services in Law No. 12 of 1995 mentions that one of the rights of inmates is "to get health services and proper food". But in contrast to the conditions on the ground with the application of the law is difficult to implement. Departing from this, the question arises: How is the fulfillment of health rights for fostered citizens in The Class IIA Banceuy Bandung Correctional Institution based on Law No. 12 of 1995 on Correctional Services? Whatis the concept of good development of health rights to the built citizens in The Correctional Institution Class IIA Banceuy Bandung based on Law No. 12 of 1995 on Correctional Services? . Research on thesis writing uses empirical juridical methods with sampling techniques. The data collection techniques used include observations, interviews and documentation. The results of this study show that the fulfillment of the health rights of lapas residents Class II-A Banceuy Bandung can be said to be insufficient due to lack of medical personnel and or not in accordance with Permenkumham No.M.HH.02.UM.06.04 of 2011,and not in accordance with article 17 paragraph 4 of PP No. 32 of 1999 related to health care outside LAPAS. This requires that the governmentcanbe more careful in understanding the context of the laws and regulations and their derivative regulations at the level of implementation related to the fulfillment of health rights for the citizens can be carried out in accordance with the applicable. Abstrak. Dalam proses menegakan hukum bagi pelaku kejahatan agar terintegrasi kembali dimasyarakat melalui Lembaga Pemasyarakatan merupakan tempat melaksanakan pembinaan Narapidana. Pasal 12 UU No.12 tahun 1995 tentang Pemasyarakatan mewajibkan setiap narapidana mendapatkan tempat tinggal yang layak, hak untuk mendapatkan makanan yang bergizi juga hak untuk mendapatkan pelayanan kesehatan.” Selanjutnya dengan pelayanan kesehatan didalam UU No. 12 Tahun 1995 menyebutkan bahwa salah satu hak narapidana ialah “mendapatkan pelayanan kesehatan dan makanan yang layak”. Namun pada praktiknya penerapan undang-undang dirasa sulit dilaksanakan. Berangkat dari hal tersebut maka timbul pertanyaan: Bagaimana pemenuhan hak kesehatan bagi warga binaan di Lembaga Pemasyarakatan Kelas IIA Banceuy Bandung dihubungkan UU Nomor 12 Tahun 1995 Tentang Pemasyarakatan? Serta Bagaimana konsep pembinaan yang baik atas hak kesehatan terhadap warga binaan di Lembaga Pemasyarakatan Kelas IIA Banceuy Bandung dihubungkan UU Nomor 12 Tahun 1995 Tentang Pemasyarakatan?. Penelitian pada penulisan skripsi ini menggunakan metode yuridis empiris dengan teknik sampling. Teknik pengumpulan data mengunakan observasi, wawancara. Hasil dari penelitian menunjukan bahwa pemenuhan hak kesehatan wargabinaan LAPAS Kelas II-A Banceuy Bandung belum cukup memadai dikarenakan kurangnya tenaga medis dan atau tidak sesuai dengan Permenkumham No. M.HH.02.UM.06.04 Tahun 2011, dan tidak sesuai pasal 17 ayat 4 PP No. 32 Tahun 1999 terkait penanganan kesehatan diluar LAPAS. Hal ini mengharuskan pemerintah dapat lebih teliti melihat kondisi dilapangan.